How Can Flipped Learning Continue in a Fully Online Environment? Lessons Learned During the COVID-19 Pandemic. Issue 2 (7th February 2023) - Lo, Chung Kwan
ABSTRACT: Teachers and students had an unusual experience in 2020. Due to the outbreak of the COVID-19 pandemic, regular teaching and learning in schools were suspended in many countries. The prolonged school closure presented unprecedented challenges because all teaching and learning activities had to be converted to a fully online format. This article reports on an attempt to sustain flipped learning using real-time online instruction. A flipped lesson on the cross-disciplinary applications of linear systems (i.e., balancing chemical equations) is presented in detail. Student feedback and the lessons learned from the experience are discussed.